A clinical study of incidence of malignancy in solitary thyroid nodule in a tertiary care hospital - V., Palani; S., Reshma (International Surgery Journal, 2018)
Background: Thyroid nodules are common endocrine problem. A discrete swelling in an otherwise impalpable gland is termed as solitary nodule of thyroid. Solitary nodules have a high likelihood of being malignant. They should be characterized properly for optimum management. Aim of the study is to identify the incidence of malignancy in solitary nodule thyroid. Methods: A prospective study had been carried out from January 2018 to October 2018, in the Department of General surgery, ACS Medical College and Hospital, Chennai, India. Fifty patients, who presented with solitary thyroid swelling were examined clinically and confirmed after taking a detailed history and underwent thyroid surgery were included in this study. The histopathological reports were evaluated by standard statistical methods. Results: There were 50 cases of clinically detected solitary thyroid nodule with female preponderance more than males. The mean age of the incidence of solitary thyroid nodule is 35years. The incidence of malignancy in solitary thyroid nodule is 20%. Conclusions: It is concluded from the present study that 20% of solitary thyroid nodules are malignant, with female preponderance and a mean age of solitary thyroid nodule is 35years.